2021
DOI: 10.1111/anu.13272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protein enriched co‐products originating from wheat fermentation in diets of common carp Cyprinus carpio to examine effects on growth response, mineral retention, haematological status and intestinal integrity

Abstract: Six experimental isonitrogenous (380 g kg -1 crude protein) and isolipidic (80 g kg -1 ) diets were formulated for juvenile carp Cyprinus carpio. The fish meal protein component of a basal diet (control treatment) was effectively replaced by yeast protein concentrate unrefined (YPC U ), yeast protein concentrate refined (YPC R ), yeast protein concentrate potable alcohol (YPCPA) at 300 g kg -1 of total dietary protein originating from a novel wheat fermentation process. Distillers dried grains with solubles (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The nutrient digestibility (ADC) of a feed ingredient is an important factor in evaluating the nutritive value of the ingredient because it is related to the quantity of the nutrient absorbed by the fish (Fang et al, 2016). As a result, the digestibility coefficients for respective nutrients, particularly protein, EAA, and energy, are one of the most important aspects of any new feed ingredient (Omar et al, 2021;Sándor et al, 2021 a). The nutri-ent digestibility of DDGS is dependent on the digestive ability of the non-protein energy fraction.…”
Section: Effect Of Ddgs On Nutrient Digestibility In Fish and Crustac...mentioning
confidence: 99%
See 1 more Smart Citation
“…The nutrient digestibility (ADC) of a feed ingredient is an important factor in evaluating the nutritive value of the ingredient because it is related to the quantity of the nutrient absorbed by the fish (Fang et al, 2016). As a result, the digestibility coefficients for respective nutrients, particularly protein, EAA, and energy, are one of the most important aspects of any new feed ingredient (Omar et al, 2021;Sándor et al, 2021 a). The nutri-ent digestibility of DDGS is dependent on the digestive ability of the non-protein energy fraction.…”
Section: Effect Of Ddgs On Nutrient Digestibility In Fish and Crustac...mentioning
confidence: 99%
“…The concentration and functional forms of minerals need to be maintained within narrow ranges for essential metabolic activities in cells, tissues, and organs for fish. Recently, results of studies showed the increased inclusion of DDGS increases the tissue retention levels of some minerals (Omar et al, 2021;Anwar et al, 2020). Øverland et al (2013) reported that a diet including DDGS promoted better phosphorus retention compared with a fish meal-based reference diet for rainbow trout.…”
Section: Effect Of Ddgs On Nutrient Digestibility In Fish and Crustac...mentioning
confidence: 99%
“…Studies have shown that fish with a higher gut surface area or longer intestine tend to exhibit higher FCE, indicating their enhanced ability to digest and absorb nutrients from the feed [60,61] Moreover, the relationship between FCE and phosphorus pollution in aquaculture is crucial. Low FCE is associated with decreased phosphorus retention efficiency in farmed fish, resulting in increased phosphorus excretion into the water [62][63][64][65][66][67][68]. Understanding this relationship enables the creation of effective management strategies to reduce phosphorus pollution in aquaculture systems.…”
Section: Relationship Between Fish Gut Structure and Feed Conversion ...mentioning
confidence: 99%